Ramnad White sheep—Phenotypic and genetic characterization - Raja, K N; Jain, A; Singh, G; Kumar, Luv; Yadav, H K; Arora, R (The Indian Journal of Animal Sciences, 2012)
The phenotypic and genetic characterization of Ramnad White, an important mutton type sheep breed of Tamil Nadu state is presented. The animals are medium sized with hairy fleece and predominantly white coat colour. Average flock size is 113. Measurements were recorded for body weight, body length, height at withers, chest girth, paunch girth, ear length, horn length and tail length in 290 adult animals. The genetic variability in 57 DNA samples of Ramnad White breed using microsatellite markers was assessed in terms of observed number of alleles, observed heterozyosity, expected heterozygosity and within breed heterozygote deficiency (FIS). A total of 232 alleles were identified across the 24 markers. The average estimates of allele diversity (9.667), observed heterozygosity (0.708) and gene diversity (0.759) elucidated substantial genetic diversity within Ramnad White breed. Within population inbreeding estimates (FIS) for investigated population (0.068) showed a low rate of inbreeding.